Nation and the construction of masculinities in the Film Seperti Dendam Rindu Harus Dibayar Tuntas - Sari, Genny Gustina; Udasmoro, Wening; Noviani, Ratna (Universitas Negeri Yogyakarta, 2025)
Films often represent masculinities influenced by social constructions produced and legitimised by the state. This research examines how the state shapes multiple forms of masculinity through the film Seperti Dendam Rindu Harus Dibayar Tuntas. The film critiques the hegemonic masculinity constructed by the state, while also illustrating that masculinity is not monolithic. Instead, it consists of diverse and sometimes conflicting contextually negotiated constructions. This study uses multimodal discourse analysis to explore the interrelationship between the state, masculinities, and gender representation within the film. The findings reveal that the state plays a significant role in maintaining hegemonic masculinity through policies and regulations that reinforce patriarchal norms. However, the film also opens up spaces for renegotiation, particularly for heterosexual men who fail to conform to dominant standards, allowing them to reclaim recognition within the masculine hierarchy. Furthermore, the film, produced in the Reformation era, set in the Orde Baru era, reflects a transitional moment where representations of masculinity become more fluid and contested. In a patriarchal system, while masculinity is still maintained through social control mechanisms, its boundaries are increasingly permeable, enabling cultural shifts and new gender negotiations. This research contributes to gender and media studies by showing how films, particularly Seperti Dendam Rindu Harus Dibayar Tuntas, can challenge and disrupt patriarchal constructions of masculinity shaped by the state, thereby opening up new avenues for understanding and redefining masculinity.